A history of singing - Potter, John; Sorrell, Neil. (Cambridge Cambridge University Press, 2012)
From its prehistoric past to its multicultural present, this history examines singing as a historical and universal phenomenon.
France and the chanson tradition
Electronic reproduction.
Keywords: Singing -- History; Choral singing -- History; Vocal music -- History and criticism; Electronic books